A Novel Hybrid Yellow Saddle Goatfish Algorithm for Fuel Consumption Vehicle Routing Problem with Simultaneous Pick-up and Delivery Problem - Dana Marsetiya Utama; Ulfa Fitriani; Ikhlasul Amallynda; Rizal Dian Azmi (Jurnal Teknik Industri, 2022)
Currently, the issue of the fuel crisis has become a global concern. The distribution sector is one of the sectors that consume the most significant fuel. Therefore, an effective procedure for fuel energy efficiency is needed to resolve the routing problem. In addition, the vehicle load must be considered in delivery and pickup at each node. This research proposes the novel Hybrid Yellow Saddle Goatfish Algorithm (HYSGA) algorithm to solve the Fuel Consumption Vehicle Routing Problem Simultaneous Pickup and Delivery (FCVRPSPD) problem. The objective function to be achieved was to minimize fuel costs. This study conducted experiments with HYSGA parameters such as the number of Goatfish, iterations, and the number of goatfish clusters to optimize the FCVRPSPD problem. In addition, a sensitivity analysis was presented to examine the effect of the FCVRPSPD variable on fuel costs. This study also compared the proposed algorithm with several state-of-the-art procedures. The results showed that the parameters of the number of Goatfish and the HYSGA iteration affected fuel costs. Furthermore, based on experiments, the proposed algorithm provided a competitive fuel cost compared to other algorithms.